Poetic Lithuania of Miłosz - Berkan-Jabłońska, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article deals with the images of Lithuania found in Czesław Miłosz’s poetry. The novels and essays have only been used to confirm the conclusions drawn from the interpretation of selected poems. Despite the frequently-declared unwillingness of the author of Dolina Issy (The Valley of the Issa) to accept and use any autobiographical elements in literature, the land of his childhood has always been present in all the poet’s works. The explanation of this fascination with nostalgia seems to be unsatisfactory. The author of the article perceives the poetic images of Lithuania created by the uprooted immigrant as a symbol of his inner, not purely geographical, settlement. The subject of the discussion is the ever-changing perception of the Eastern-Borderland, which corresponds to particular stages of the protagonist’s journey through life. The starting point is the experience of eviction. It modifies the originally idealized vision of the “little homeland” and makes the hero’s attempt to reject or “amputate” it. The poems from the Światło dzienne (Daylight) collection surprise the reader by a hostile attitude towards the poet’s youth spent in Lithuania and the perception of those early memories as some destructive forces threatening the artist. It is only after a many years’ quest that the borderland heritage is appreciated and conquered again. Now, however, it acquires a different, more symbolic form. The cycle Miasto bez imienia (A Town without a Name) and the poem Gdzie wschodzi słońce i kędy zapada (Where the Sun Rises and Sets) are evidence of a gradual transformation. The faithful recreation in the poet’s memory of particular places and people changes into the construction of some outside religious space, built from the traces of the real world. Lithuania changes into a perfect reality, a Super-Land, capable of retaining the past and combining it with the present. It is a prop freeing the poet from the waste land of Urizen.